The Distribution Channel Preferences in Purchase Decision-Making of Backpacker Hostel Customers - Aditia Sovia Pramudita; Muhammad Ardhya Bisma; Darfial Guslan (Bina Nusantara University, 2020)
The research aimed to find the correlation between distribution channels to each purchase decision-making process in hostel buying. This research was quantitative research using questionnaires to gather the data from 349 respondents. Linear regression analysis was used to analyze the data to find the correlation between each variable. The result shows that Online Travel Agent (OTA) has a significant and positive relationship to every purchase decision-making process. Then, go-show has only a significant and positive correlation in the purchase decision step. Meanwhile, the company’s website has a significant and positive relationship to purchase decision and postpurchase behavior steps. Last, the travel agent has no positive correlation to any of the customer decision-making process. Based on those facts, OTA remains the first choice of customers in terms of hostel buying.